Kunci Kemajuan Pertanian Indonesia: Pandangan Generasi Muda: The Key to Indonesia's Agricultural Progress: A Young Generation's View - Puteri, Adinda N. J.; Rozaki, Zuhud; Wulandari, Retno; Suryani, Cahyaningrum A. (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2024)
Agriculture in Indonesia plays an important role in the economy and the welfare of society. This paper reviews the strategic role of the younger generation in developing the agricultural sector. The younger generation brings innovation through the application of modern technology, such as digital equipment and smart farming applications, to improve efficiency and productivity. They also encourage sustainable agricultural practices and organic farming, contributing to national food security as well as protecting the environment. In the context of sustainable development, young people need to receive training and education before entering agriculture, utilising technology and digital resources. Promotions and campaigns that encourage young people to take an active role in modern agriculture are also needed. Government policy support, agricultural technology development, entrepreneurship, preservation of natural resources, inter-sectoral collaboration, export markets, and wise direction of social media are also key measures. The challenges faced by the younger generation include the development of modern farming techniques, so they need to have adequate curiosity and skills. The positive thinking of the younger generation, especially in relation to agriculture, can be a driver for the nation's progress. Therefore, engaging the younger generation wisely in agriculture is key to advancing the sector and improving people's welfare.